Analisis Perubahan APBDES Tahun 2020 dan 2021 di Desa Sayang, Kecamatan Jatinangor, Kabupaten Sumedang - Fi'la Al Farisi; Ramadhan Pancasilawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The objective of this research is to identify the aspects that underwent changes in the Village Revenue and Expenditure Budget (APBDes) for the years 2020 and 2021 in the Sayang Village, Jatinangor Subdistrict, Sumedang Regency. This is particularly important due to the impact of the Covid-19 pandemic in Indonesia during those years, which is expected to influence changes in the APBDes. The research methodology employed is qualitative descriptive method, with field study as the data collection technique. The results obtained from the analysis of changes in the Village Revenue and Expenditure Budget (APBDes) for the fiscal years 2020 and 2021 indicate alterations in both revenue and expenditure budgets, including both increases and decreases. This is attributed to the onset of the COVID-19 pandemic in 2020, with the budget being directed towards disaster response, emergency, and urgent areas. In 2021, there is a positive phenomenon in budget changes, with the majority experiencing increases focused on improving healthcare services. Similar to the fiscal year 2020, there were no changes in financing for the fiscal year 2021.